(untitled) (International journal of artificial intelligence, 2026)
This article provides a methodological framework for pre-service foreign language (FL) teachers participating in the "Online TFL Workshops" video contest. It examines the role of self-study in credit-module training, illustrating how autonomous inquiry facilitates the integration of digital tools into FL teaching. The guide details specific requirements for high-scoring projects, including a 15-student role-allocation plan and a 5-step digital tool integration procedure. By emphasizing curriculum alignment, data-driven error correction, and professional production standards, this framework offers a roadmap for converting theoretical knowledge into high-fidelity instructional videos for professional development.